2017
DOI: 10.15835/nbha45110709
|View full text |Cite
|
Sign up to set email alerts
|

Alleviation of Drought Stress in White Clover after Inoculation with Arbuscular Mycorrhizal Fungi

Abstract: White clover is extremely susceptive to drought stress (DS), while it is not clear whether arbuscular mycorrhizal fungi (AMF) enhance drought tolerance of the plant. This study was carried out to evaluate effects of two AMF species, Funneliformis mosseae and Paraglomus occultum, on flavonoid, soluble protein, proline, and nutrient uptake in roots of white clover under well-watered (WW) and DS conditions. Root colonization by F. mosseae and P. occultum was heavily decreased by 7-week DS treatment. Mycorrhizal p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 22 publications
2
6
0
Order By: Relevance
“…The present study showed a dramatic reduction in root AMF colonization of tea plants under DS conditions as compared with tea plants under WW conditions, which is consistent with the results by Amiri et al (2015), Tuo et al (2017), andZhang et al (2020), who observed a significant decrease of mycorrhizal colonization in citrus, geranium, and white clover under water deficit conditions. Probably, water deficit inhibited the germination rate of spores, restricting the extension and colonization ability of AMF hyphae (Huang et al, 2017).…”
Section: Discussionsupporting
confidence: 93%
“…The present study showed a dramatic reduction in root AMF colonization of tea plants under DS conditions as compared with tea plants under WW conditions, which is consistent with the results by Amiri et al (2015), Tuo et al (2017), andZhang et al (2020), who observed a significant decrease of mycorrhizal colonization in citrus, geranium, and white clover under water deficit conditions. Probably, water deficit inhibited the germination rate of spores, restricting the extension and colonization ability of AMF hyphae (Huang et al, 2017).…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, this finding agrees with a study conducted by Pedranzani et al [23], where Digitaria eriantha plants were inoculated with R. irregularis and subjected to drought, salinity, and cold stress. In contrast, water stress decreases the root colonization of different AMF with plant species such as soybean [48], rice [49], Ocimum gratissimum [50], Trifolium repens [51], and Triticum aestivum [52]. Interestingly, Pearson correlation analysis in our study illustrated that mycorrhizal colonization had a close correlation with some defense enzyme activities, and a negative association with H 2 O and MDA levels under both combined stresses (Tables S1 and S2), highlighting the role of AMF in ROS metabolism in the host plants exposed to such simultaneous abiotic stresses.…”
Section: Discussionmentioning
confidence: 99%
“…They form mutualistic symbioses with roots of more than 80% of terrestrial plants [5]. Abundant research has identified that AMF could enhance the ability of plants such as apple [6], citrus [7,8], maize [9], white clove [10], Zenia insignis [11], Knautia arvensis [12], wheat [13], carob [14], rice [15], rose [16], and blueberry to cope with water stress [17]. The mechanisms behind this action include the enhancement of apples' drought tolerance by improving their gas exchange capacity, increasing chlorophyll fluorescence parameters, creating a greater osmotic adjustment capacity, increasing the scavenging of reactive oxygen species (ROS), and using MAPK signals for interactions between AMF and their apple plant hosts [6].…”
Section: Introductionmentioning
confidence: 99%
“…Citrus tolerance to drought is improved based on improved water uptake via extended extraradical hyphae, improving nutrient uptake, better root system architecture, polyamine regulation, higher osmotic adjustments, developed enzymatic and non-enzymatic antioxidant defense systems, and improving glomalin-induced soil structural development [7,8].Drought tolerance is improved in maize by improving chlorophyll content, improving mineral uptake and assimilation, increasing growth and photosynthesis, increasing the content of compatible solutes, up-regulating the antioxidant system, and eliminating ROS, which leads to the protection of major metabolic pathways [9]. Enhanced drought tolerance in white clove is led by greater nutrient absorption and the accumulation of protective substances (soluble protein, proline, and flavonoids) [10]. A positive effect on plant biomass, osmolytes, and antioxidant enzyme activity under drought was noted in Zenia insignis [11], while alleviating the effect of AMF on Knautia arvensis drought stress was supported by lower proline accumulation [12].…”
Section: Introductionmentioning
confidence: 99%